(untitled) (Dhaka University Journal of Science, 2015)
In the present study, a technique to remove arsenic has been developed with a polymer-supported hydrated Fe(III) oxide (HFO) by using a strongly basic anionic exchanger IRA-420 as the host material and FeCl3-HCl-NaCl solution as the reaction environment. The optimized conditions were applied to a sample collected from Sonargaon, Dhaka. The removal efficiency of this method was more than 80%, which indicates that this method can be used as an efficient method for arsenic removal in Bangladesh. IRA-420-HFO exhibits more preferential adsorption of arsenic ions which is attributed to the Donnan membrane effect exerted by the host resin (IRA-420) as well as to the loaded HFO particles for specific interaction toward arsenic (III) ions. All the results indicated that HFO polymer derivative is an attractive adsorbent for efficient arsenic (III) removal from contaminated groundwater of Bangladesh. Dhaka Univ. J. Sci. 63(2):85-89, 2015 (July)